2021
DOI: 10.1002/pon.5844
|View full text |Cite
|
Sign up to set email alerts
|

Exploring primary breast cancer survivors' self‐management of sustained cancer‐related cognitive impairment in the workplace

Abstract: Objective Work plays a central role in return to a more ‘normal’ life among women diagnosed with primary breast cancer. However, ongoing cancer‐related cognitive impairment (CRCI) and cancer‐related sequelae continue to detrimentally impact workability. Only a few studies have explored the long‐term consequences of CRCI and self‐management coping strategies applied in the workplace. This study explored women's experiences of sustained post‐treatment CRCI and its impact on workability beyond the initial return‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…As mentioned, we found that women with a greater quality of working life experienced better perceived cognitive functioning; this is an important finding as our earlier work has shown that reduced self-reported cognitive function adversely affects workability, general emotional health and work-related confidence in women with a history of primary breast cancer [ 29 ]. Collectively our findings indicate that greater quality of working life may play an influential role in enhancing workability by increasing perceived cognitive function in working women with MBC.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…As mentioned, we found that women with a greater quality of working life experienced better perceived cognitive functioning; this is an important finding as our earlier work has shown that reduced self-reported cognitive function adversely affects workability, general emotional health and work-related confidence in women with a history of primary breast cancer [ 29 ]. Collectively our findings indicate that greater quality of working life may play an influential role in enhancing workability by increasing perceived cognitive function in working women with MBC.…”
Section: Discussionmentioning
confidence: 54%
“…It is plausible that our findings in working women may be connected to reduced career progression and work opportunities following MBC diagnosis. Our earlier work has shown career progression is at a standstill for many primary breast cancer survivors as a result of the effects from post-treatment sequelae [ 29 ]. Similar research should explore career development and opportunities in women living with MBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that some of the changes experienced with the self‐management methods may have been driven by women's reflections after the baseline interviews and their (un)conscious decision to make improvements. Given that Chapman et al (2021) identified that some women find cognitive support methods applied in the workplace to be problematic and to contribute to emotional distress, these findings also have important implications.…”
Section: Discussionmentioning
confidence: 96%
“…However, results from qualitative studies have shown that various emotions may characterize the different stages of the return to work process that are sometimes pleasant, sometimes unpleasant and sometimes experienced together [emotional ambivalence] (Larsen et al, 2001 ). Cancer survivors may experience this particular state of emotional ambivalence, such as fear together with relief when disclosing their disease state to their manager, or pride to be able to continue working combined with frustration due to reduced cognitive capacities when maintaining work (Robinson et al, 2015 ; Chapman et al, 2022 ). Tiedtke et al ( 2011 ) have also found fundamental differences in how cancer survivors perceive their work disability, for example, some will focus on life after treatment, while others feel overwhelmed and exhausted, partly related to intense and alternating emotions.…”
Section: Introductionmentioning
confidence: 99%